Native American Sovereignty in Maine - Brimley, Stephen (Maine Policy Review, 2004)
The nationally unique 1980 Maine Indian land claims settlement brought benefits to three of Maine’s tribes—the Penobscot Nation, Passmaquoddy Tribe, and Houlton Band of Maliseets. However, serious problems remain with the economic, health, and educational status of tribal members. Moreover, another group, the Aroostook Band of Micmacs, was not included in the original settlement. Brimley’s analysis of Native American sovereignty in Maine reviews the foundation of the land claims settlement, how it came to be enacted, its terms, and its impact on Maine’s tribes. He notes how the recent failure of tribal efforts to build a casino in the southern part of the state has exacerbated already-strained state-tribal relations.
Keywords: Maine; Native American sovereignty; Maine Indian land claim settlement